The effectiveness of narrowband ultraviolet b phototherapy for the treatment of moderate to severe psoriasis in adult patients - Rahmawati, Hutami Rizki; Djuanda, Stephanie Deborah; Ainun, Helena Azhar; Winditia, Shafira Aghnia; Martani, Devanie (Science Midwifery, 2024)
Psoriasis is a chronic skin condition influenced by genetics and the environment. It affects 57.8 per 100.000 people in 2019. The severity of psoriasis is assessed using the Psoriasis Area Severity Index (PASI), with scores above 10 indicating moderate to severe disease. Treatment options for psoriasis including systemic therapies and phototherapy. Patient satisfaction remains suboptimal, with adherence rates to systemic therapy as low as 40%. Narrowband ultraviolet B (NB-UVB) phototherapy is preferred for its safety. This review aims to evaluate the effectiveness of NB-UVB phototherapy in treating moderate-to-severe psoriasis in adults. Descriptive analysis was the method that journal used, search of online databases was conducted and found 12 relevant articles meeting criteria, published in English between 2014 and 2024, focusing on patients with moderate to severe psoriasis receiving NB-UVB phototherapy. Our review found that NB-UVB phototherapy, whether used alone or in combination with adjuvants, effectively treats moderate to severe psoriasis vulgaris in adult patients. Combining NB-UVB with adjuvants can further improve its effectiveness. However, further research is needed to assess its effectiveness across different age groups and to optimize treatment strategies based on individual patient characteristics and disease severity.